2022
DOI: 10.1007/s00203-022-02834-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Enterococcus faecium LM5.2 for lipopeptide biosurfactant production and its effect on the growth of maize (Zea mays L.)

Abstract: The lipopeptide biosurfactants' chemical characteristics from the lactic acid bacteria isolated from milk and milk products were studied and their effect on maize plant growth. The oil displacement test was performed as a primary screening method to select the BS producing bacteria. Enterococcus faecium LM5.2 had the maximum emulsi cation index of 45.1±3 and reduced the surface tension to 32.98 ± 0.23% among all the isolates. E. faecium LM5.2 e ciently produced 945.26 ± 4.62 mg/l biosurfactants within 48 hours… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…Furthermore, this study revealed the growth-promoting properties of E. italicus ONU547 for microclones during the transition from in vitro conditions to a nonsterile environment. Moreover, our experiments demonstrated the positive effects of inoculating with cell suspensions of the microorganisms rather than their purified metabolites, as often reported in the existing literature (Lee et al, 2015 ; Pellegrini et al, 2020 ; Chaurasia et al, 2022 ; Msimbira et al, 2022 ). This indicates that for the potential development of biological preparations based on E. italicus ONU547, there is an opportunity to save time by bypassing the isolation and purification of specific synthesized compounds and simply utilizing the cell mass.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, this study revealed the growth-promoting properties of E. italicus ONU547 for microclones during the transition from in vitro conditions to a nonsterile environment. Moreover, our experiments demonstrated the positive effects of inoculating with cell suspensions of the microorganisms rather than their purified metabolites, as often reported in the existing literature (Lee et al, 2015 ; Pellegrini et al, 2020 ; Chaurasia et al, 2022 ; Msimbira et al, 2022 ). This indicates that for the potential development of biological preparations based on E. italicus ONU547, there is an opportunity to save time by bypassing the isolation and purification of specific synthesized compounds and simply utilizing the cell mass.…”
Section: Discussionsupporting
confidence: 85%
“…In other studies investigating the effects of enterococci on plant growth, different concentrations of bacteria, inoculation procedures, and plant species were employed, resulting in varying observed influences. For example, Chaurasia et al ( 2022 ) inoculated soil with Enterococcus spp. at a concentration of 8 × 10 5 CFU/kg, leading to maize seed germination occurring three days faster than in the control group and a 53.7% increase in plant height, while no significant difference in the number of leaves was observed.…”
Section: Discussionmentioning
confidence: 99%
“…According to Anschau standard curve the lipid content was 33% and the concentration of the protein was 28.5%, according to an analysis of the protein's absorbance using the Bradford standard curve. These results compared with Chaurasia et al, 34 who reported that biosurfactant produced by E. faecium LM5 consisted of Lipid and peptides.…”
Section: Results and Disscusionsupporting
confidence: 74%
“…While Lara et al, 34 mentioned that the biosurfactant produced by Lactiplantibacillus plantarum Tw226 consisted of protein as the main part (64%), then Lipids (21%), and carbohydrate (21%).…”
Section: Results and Disscusionmentioning
confidence: 99%